End-to-end validation of the geometric dose delivery performance of MR linac adaptive radiotherapy. (11th February 2021) - Bernchou, Uffe; Christiansen, Rasmus L; Bertelsen, Anders; Tilly, David; Riis, Hans L; Jensen, Henrik R; Mahmood, Faisal; Hansen, Christian R; Hansen, Vibeke N; Schytte, Tine; Brink, Carsten
Abstract: The clinical introduction of hybrid magnetic resonance (MR) guided radiotherapy (RT) delivery systems has led to the need to validate the end-to-end dose delivery performance on such machines. In the current study, an MR visible phantom was developed and used to test the spatial deviation between planned and delivered dose at two 1.5 T MR linear accelerator (MR linac) systems, including pre-treatment imaging, dose planning, online imaging, image registration, plan adaptation, and dose delivery. The phantom consisted of 3D printed plastic and MR visible silicone rubber. It was designed to minimise air gaps close to the radiochromic film used as a dosimeter. Furthermore, the phantom was designed to allow submillimetre, reproducible positioning of the film in the phantom. At both MR linac systems, 54 complete adaptive, MR guided RT workflow sessions were performed. To test the dose delivery performance of the MR linac systems in various adaptive RT (ART) scenarios, the sessions comprised a range of systematic positional shifts of the phantom and imaging or plan adaptation conditions. In each workflow session, the positional translation between the film and the adaptive planned dose was determined. The results showed that the accuracy of the MR linac systems was between 0.1 and 0.9 mm depending on direction. The highest mean deviance observed was in the posterior–anterior direction, and the direction of the error was consistent between centres. The precision of the systems was related to whether the workflow utilized the internal image registration algorithm of the MR linac. Workflows using the internal registration algorithm led to a worse precision (0.2–0.7 mm) compared to workflows where the algorithm was decoupled (0.2 mm). In summary, the spatial deviation between planned and delivered dose of MR-guided ART at the two MR linac systems was well below 1 mm and thus acceptable for clinical use.